Evidence in Support of the Border-Ownership Neurons for Representing Textured Figures - Han, Chao (iScience, 2020)
We presented one eye with a monocular-boundary-contour (MBC) square, created by phase-shifting a central region of grating relative to a larger uniform grating surround, and the fellow eye with the larger uniform grating. In addition, the grating within the MBC region was rendered with lower contrast relative to the remaining stimulus. Despite this, we found the lower contrast MBC region dominated the perceived cyclopean contrast, with the corresponding region in the fellow eye being suppressed. Secondly, we found for dichoptic stimuli with half-images having square grating regions of different BC strengths, the interocular BC strength ratio determined the perceived contrast of the cyclopean square. Thirdly, we found perceived spatial phase of the cyclopean square was dominated by the spatial phase of the MBC half-image. Altogether, these psychophysical findings provided evidence for a border-to-interior representation strategy, that constructing surface begins at the boundary contour (BC), in binocular contrast and phase integration.